Struktur Komunitas Plankton sebagai Indikator Kualitas Perairan Budidaya di Tambak Lorok Semarang - Makhfudhoh, Dzunnuroini Khanif; Hidayat, Jafron Wasiq; Muhammad, Fuad (Bioma : Berkala Ilmiah Biologi, 2018)
Plankton is organisms that had an important role in water as natural feed of fishes and as an indicator. This study aimed to identify water quality which was suitable for fish cultivation reviewed from physics-chemicals parameters of water and its saprobic status in Tambak Lorok Tanjung Mas Kota Semarang. Sampling were take based on 5 stations that could represented from plankton variety of condition water stability . Plankton samples were by using net plankton number 25, then preserved with alcohol 70% and formalin 4%. Variables of ponds water quality measured were temperature, salinity, dissolved oxygen, pH, turbidity, N concentration, and Pb content. Identification of planktons used SRC method under microscop. The result of plankton analysis in Tambak Lorok water showed 42 phytoplankton species, the commonly species found are Coscinodiscus centralis, Coscinodiscus granii, Gyrosigma sp., Navicula radiosa, Pandorina sp., and Melosira sp. Meanwhile, zooplankton found was 22 species with common species are Cyclops, Harpaticoida, Tricodesmium evythraeum, Brachinus plicatilis, and Lensia subtilis. Phytoplankton diversity index are 0.057-0.367 and equity index are 0.025-0.176. Zooplankton diversity index are 0.247-0.360 and equity index are 0.157-0.201. This indices showed that there were low level of species diversity and community stability, dominance since the species occurred. Measurement of water quality variables indicated that Tambak Lorok had been contaminated and needed a preliminary management before d be used as fish cultivation ponds, because the analysis result was not appropriate with Government water quality  regulation. Based on the measurement, soprobic index categories on α/β-Mesosaprobic to Oligosaprobic phase and the degree of pollution is very mild to moderate. Keywords :  Community Structure, plankton, Tambak Lorok, Tanjung Mas, Semarang